2015
DOI: 10.1103/physrevc.91.044611
|View full text |Cite
|
Sign up to set email alerts
|

Yields of neutron-rich nuclei by actinide photofission in the giant dipole resonance region

Abstract: Photofission of actinides is studied in the region of nuclear excitation energies that covers the entire giant dipole resonance (GDR) region. A comparative analysis of the behavior of the symmetric and asymmetric modes of photon induced fission as a function of the average excitation energy of the fissioning nucleus is performed. The mass distributions of 238 U photofission fragments are obtained at the endpoint bremsstrahlung energy of 29.1 MeV which corresponds to mean photon energy of 13.7±0.3 MeV that coin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It is apparent from Fig. 1 that the Lorentz line shape fitting is quite accurate which reflects the fact that the uncertainties in the parameters [22] are quite small. The ratio method predictions for photofission are almost as good upto the first GDR peak whereas it is off by about ten percent near the second GDR peak, but still provides much better predictions than that calculated by the TALYS code which underestimates as well as fails to reproduce the shape, or by the evaporation-fission process of the compound nucleus which although retains more or less the shape of the curve but overestimates [24] the photofission cross sections at these energies.…”
Section: Theoretical Framework Of Photonuclear Reactionmentioning
confidence: 75%
See 2 more Smart Citations
“…It is apparent from Fig. 1 that the Lorentz line shape fitting is quite accurate which reflects the fact that the uncertainties in the parameters [22] are quite small. The ratio method predictions for photofission are almost as good upto the first GDR peak whereas it is off by about ten percent near the second GDR peak, but still provides much better predictions than that calculated by the TALYS code which underestimates as well as fails to reproduce the shape, or by the evaporation-fission process of the compound nucleus which although retains more or less the shape of the curve but overestimates [24] the photofission cross sections at these energies.…”
Section: Theoretical Framework Of Photonuclear Reactionmentioning
confidence: 75%
“…The list of parameters σ i , E i and Γ i for i = 1, 2 extracted by fitting experimental data [20,21] are provided in Ref. [22] for both photoabsorption as well as photofission cross sections. It was found that for photoabsorption and photofission cross sections there are little changes in parameters E i and Γ i while σ i decides the difference.…”
Section: Theoretical Framework Of Photonuclear Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LD model is based on the liquid drop model mass formula, in which the nucleus is considered as an incompressible droplet and all nuclei have the same density [22,30]. The systematic model is based on the assumption that the ratio between the numbers of protons and neutrons in light and heavy fission fragments is identical to that in the fissioned nucleus [23,31]. In the LD model, = −3.8 with being the most stable isotope of fission fragments.…”
Section: B Isobaric Charge Distributionsmentioning
confidence: 99%
“…Among three, photo-fission [5] has been found more promising for having better thermal management and being a cold process creates higher yields for n-rich nuclei as compared to light ion induced fission except in the mass range of 110 < A < 125. Therefore there is a renewed interest presently to go for photo-fission [6] using e-LINAC as a primary accelerator to produce energetic photons in the Giant Dipole Resonance (GDR) region [7,8]. The Advanced Rare IsotopE Laboratory (ARIEL) [9,10] at TRIUMF, JINR, Dubna [11] and at ALTO, IPN, Orsay [12] are the laboratories, where initiative have already been taken.…”
Section: Introductionmentioning
confidence: 99%